Essentials of investments - Bodie, Zvi (McGraw-Hill/Irwin, 2007)
The market leading Essentials of Investments, 6e by Bodie, Kane and Marcus is an undergraduate textbook on investment analysis, presenting the practical applications of investment theory to convey insights of practical value. The authors have eliminated unnecessary mathematical detail and concentrate on the intuition and insights that will be useful to practitioners throughout their careers as new ideas and challenges emerge from the financial marketplace. Essentials maintains the theme of asset allocation (authors discuss asset pricing and trading then apply these theories to portfolio planning in real-world securities markets that are governed by risk/return relationships).